Dictating play to the left wing: Does soccer make you more Democratic? - Rewilak, Johan M. (Frontiers in Sports and Active Living, 2023)
There is a correlation between soccer’s popularity and States which traditionally vote Democrat in US elections. This has led to claims, where democrats lead, soccer follows. Yet this relationship may not be entirely stable, as soccer may stimulate the Democratic vote through its multicultural elements. Using the 1994 World Cup as a plausibly exogenous shock that positioned US soccer, we investigate whether US States that hosted the tournament increased their Democratic vote in future Presidential elections. A two-way fixed effects estimator and a dynamic difference-in-difference estimator shows that if a US State was a 1994 World Cup host, it increased its Democratic vote share. However, when examining Major League Soccer franchises, this relationship breaks down, but is recovered when investigating the women’s World Cup in 1999 and 2003. As the swing states of Florida and Georgia are hosting 2026 World Cup matches, the findings may hold key insights for the 2028 Presidential election.